Studi Persepsi Terhadap Hambatan Glass Ceiling, Strategi Pengembangan Karir dan Tingkat Promosi Pejabat Perempuan di Daerah Istimewa Yogyakarta - Titiek Mulyaningsih (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2014)
This study aimed to explore which of five strategies had most positively affected women’s career advancement into senior executive positions. Career advancement identified by the frequencies of formal promotion, and the five strategies are: (1) Internal Networking; (2) Career Mentoring; (3) Advanced Education and Training; (4) Career Tracking; and (5) Exceeding Performance Expectations. Contrary to this strategies women are faced to some constraints as a Glass Ceiling problem: (1) Gender; (2) Discrimiation; (3) Organization policies; (4) Individual values and (5) Social values. This Research conducted in Yogyakarta Province with 62 respondents, government servant and private company employees.The multiple regression methodology used in this study determined which strategies had most positively correlated and affected women’s career advancement and in contrast to the constraints. As a result of multiple regression analysis, Internal Networking was identified as the most effective promotional strategy. On the other hand, the gender issu was identified as the biggest problem faced to women’s career advancement.